Al-Adalah Concept in Distribution of Zakat Funds Towards Mustahiq Zakat in Lazismu Makassar City - Suarni, Agusdiwana; Kasim, Muhammad Najib; Japar, Syahrir (Jurnal Ar-Ribh, 2024)
The aim of this study is to investigate the implementation of the Al-Is concept in the distribution of zakat funds to mustahiq zakat recipients in the Lazis City Makassar. The research method employed is qualitative in nature. Data processing involves analysis of interviews conducted with staff members of Lazis City Makassar (Administrative Body Secretariat). Data collection methods include interviews, observations, and documentation studies, with the authors directly observing field conditions. The findings of this study reveal that the implementation of the Al-Is concept in distributing zakat funds to mustahiq zakat recipients in Lazis City Makassar has been carried out. However, there are variations in the allocation of funds among the eight asnaf categories. This variation reflects the principle of fairness in distributing zakat funds among the eight asnaf categories, which is determined based on the needs of each recipient category. The decision-making process regarding the allocation of funds is influenced by sharia board decisions, which may vary depending on the needs and conditions of each area.